Metallic embolus to the brain in a patient with mechanical heart valves: an extremely rare complication. Issue 8 (1st August 2019) - Sagheer, Shazib; Sheikh, Abu Baker; Hallstrom, Jon J; Raizada, Veena
Abstract : A 46-year-old man with a medical history of rheumatic valve disease underwent mitral and aortic valve replacements with On-X and CarboMedics Top Hat supra-annular mechanical valves, respectively. Seven months after the valve replacement surgery, the patient presented with dizziness. A CT scan of the brain was done as part of a thorough workup of dizziness. The CT scan revealed a small metallic density in the M2 branch of the right middle cerebral artery. The metallic density was believed to be a metallic embolus that originated from the mechanical valves or the suturing material, that is, Cor-Knot fastener. Although in our case, the dizziness was believed to be the result of benign paroxysmal positional vertigo, through this case, we aim to highlight this extremely rare structural complication of mechanical valves. This complication can have serious and potentially fatal consequences such as embolic component-related stroke or another organ infarction.